You may have something there - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
Traditional staple foods and some feed stuffs of the Pacific Islands: their chemistry, biochemistry and nutrient composition By Eroarome M Aregheore, Institute of Research, Extension and Training in Agriculture (IRETA), 2001. 65 pp. ISBN 982 175 146 76